Study on the Efficacy of Green Tea Extract on Staphylococcus aureus and Klebsiella pneumonia of Raw Chicken Meat - Kaderi, KF; Islam, MS; Sarker, T; Islam, SS; Mondol, D; Faruk, MO; Biswas, G (Meat Research, 2023)
We investigated the efficacy of green tea extract on Staphylococcus aureus and Klebsiella pneumonia of raw chicken meat. The experiment was conducted using complete randomized design (CRD) having six (6) treatments with three (3) replications. The germicidal activity was determined using the drop plate method. The results indicated that the addition of green tea extract (GTE) decreased microbial population in raw chicken meat. The lowest colony forming unit/ml (CFU ml-1) was found in T5 in 10-3 dilution factor (DF). There was a highly significant difference (p<0.001) in CFU ml-1of Staphylococcus aureus and Klebsiella pneumonia among different treatments i.e., GTE has significant effect (p<0.001) on Klebsiella pneumoniae and Staphylococcus aureus. The maximum number of Staphylococcus aureus in raw chicken meat was 14×105 CFU ml-1in T0 using TVC, while minimum was 4×104 CFU ml-1 in T5. Similar trend was also found in Klebsiella pneumoniae. GTE also showed highly significant (p<0.001) germicidal efficacy on both of Staphylococcus aureus and Klebsiell. The GTE also showed significant (p<0.01) germicidal efficacy on Staphylococcus epidermidis, Salmonella spp., Shigella spp. and E. coli. Considering the results obtained, it might be concluded that addition of 5 ml GTE reduce microbial population of raw chicken.